A cup of water under my bed : a memoir - Hernández, Daisy (Beacon Press, 2015)
A moving exploration of family, identity, and language, A Cup of Water Under My Bed is a daughter's story of finding herself and her community, and of creating a new, queer life. --Provided by publisher.